L’analyse De L’impact Des Dimensions Éthiques Et Culturelles Sur L’intégration Relationnelle Des Supply Chains : Cas Du Maroc - Akhlaffou Mohamed; Lechheb Hafsa (European Scientific Journal, ESJ, 2016)
This article aims to explore the determinants of Moroccan culture and analyze their influence on the relational integration of Supply Chains, by answering the following research question: Does Moroccan culture present favorable characteristics to the relational integration of Supply Chains? Given the fact that the relational integration of Supply Chains (Bowersox et al., 1996, 1999,2000) represents the cornerstone of the philosophy of Supply Chain Management (Mentzer et al., 2001). And since the national culture showed its influence on values and lifestyles (Sun, Horn and Merritt, 2004), on negotiations (Adair and Brett, 2005), and on behavior and ethics (Elahee, Kirby and Nasif, 2002). Consequently, we can estimate that national culture can have influence on the integration of Supply Chains and the building of trust between partners. The methodology adopted is both qualitative and quantitative, and is inscribed in the framework of moderate positivist epistemological position. The combination of methods will lead us to identify and deeply understand our research problematic.